Uso do preservativo feminino como método contraceptivo: experiências de mulheres em uma unidade de saúde no Município de Juazeiro do Norte-CE - Albuquerque, Grayce Alencar [UNIFESP] (2010)
The female condom is a form of contraception that offers to the woman major control over her body, but it is not offered most health centers, what favor the low knowledge about it. This study aimed to investigate the experiences of women assisted in a Family Health Strategy in Juazeiro do Norte city, Ceará, concerning the female condom as contraceptive. This is a exploratory and qualitative study, accomplished in April 2009, that was developed in stages: summoning of women through invitation to take part in an educational activity for submission of the material, implementation of activities, formation of small groups for a second educative meeting and after that time, individual experimentation of one unit in the nursing office to obtain initial impressions of the condom, experimentation of the posterior experimentation for a month at home and return for structured interviews. Twenty women participated in the project, most of them older than 25 years, married, an average of two children, housewife, using hormonal contraceptives. Many of them expressed surprise and astonishment at the first contact with it as a result of its model. After the use the majority reported positive impression, although they had revealed difficulties in handling and introducing it in the vaginal because of its excessive lubrication. This was considered as facilitative for the sexual act, making it more enjoyable, allowing the idealization its use of sexual fantasies. Regarding to the method, it was considered safe as contraceptive. In relation to the size, some participants reported that their sexual partners disapproved the condom, for considering it anti-aesthetic. When questioned about the contraceptive option, the women approved the female condom as contraceptive, especially in substitution of hormonal contraceptives, for they cause several collateral effects. However, this substitution is not put in practice, often for the disapproval of the partner, what disclose their necessity of obedience for financial dependency and fear of abandonment and betrayal. It is observed, then, that in practice, the female condom is tied up for the gender relations that guides norms and behaviors in the couple’s intimate life, making it difficult for women the negotiation of a safe sex. It is therefore important to assure to these women not only the contact with the female condom but also, to them and to their partners, access to educative activities that focus on gender issues, sex, sexuality, empowerment, agreements and sexual exchanges, once only for that the women can take the control of their bodies and become active in their lives’ transformation and protection.